Registration of 'Jasper' Soft White Winter Wheat. Issue 3 (25th May 2017) - Carter, A. H.; Jones, S. S.; Balow, K. A.; Shelton, G. B.; Burke, A. B.; Lyon, S.; Higginbotham, R. W.; Chen, X. M.; Engle, D. A.; Murray, T. D.; Morris, C. F.
Abstract : Many soft white winter (SWW) wheat ( Triticum aestivum L.) cultivars with high yield potential in the US Pacific Northwest lack adequate resistance to stripe rust or are only adapted to specific regions defined by annual precipitation. The objective of this research was to develop a SWW wheat cultivar with improved resistance to current stripe rust races and high yield potential across a wider range of climates. 'Jasper' (Reg. No. CV‐1124, PI 678442) SWW wheat was developed and released in September 2014 by the Agricultural Research Center of Washington State University. Jasper was tested under the experimental designations 5J061865‐11 and WA8169, which were assigned through progressive generations of advancement. Jasper is a semidwarf cultivar adapted to intermediate to high rainfall (>300 mm of average annual precipitation) wheat production regions of Washington, with acceptable yield potential in the lower rainfall areas (<300 mm of average annual precipitation). It has high‐temperature, adult‐plant resistance to the current races of stripe rust, is intermediate in height, has midseason maturity, and has an average test weight and high grain yield potential. Jasper has end‐use quality properties similar or superior to those of 'Stephens', 'Puma', and 'Otto'.